A case study on applying creative design concepts to brake rotor design. Issue 1 (7th March 2016) - Vinodh, S.; T., Sharath Kumar
Abstract : Purpose: – The purpose of this paper is to report a study in which creative design concepts have been applied to automotive brake rotor design. Design/methodology/approach: – The literature review on creative design concepts and braking system scenario has been carried out. By studying the existing brake rotors and applying creative design concepts, modified rotor designs have been developed. Findings: – The experience gained out of the study indicated that braking efficiency and durability of the braking system can be significantly improved by the adoption of proposed designs. Research limitations/implications: – The research has been carried out for an automotive passenger car. The findings of this research work could be extended to similar models of buses and trucks. Practical implications: – The usage of the proposed designs reduces the driver's effort in braking and adds significantly to the life of the rotors. Originality/value: – A case study has been reported to indicate the application of creative design concepts for enhancing the efficiency of automotive braking system in cars.